(untitled) (Hematology Meeting Reports, 2009)
Following the landmark study by Barrit and Jordan in 1960, who randomized patients with venous thromboembolism to no treatment or a combination of heparin and warfarin, antithrombotic therapy for this disease became widely accepted. Their study had to be stopped prematurely because half of the non treated patients had recurrent pulmonary embolism or died of it. Subsequent studies revealed that an initial course of heparin is really necessary. Ommitting heparin and only giving Vitamin K antagonists resulted in a 3 to 4 fold increase in the incidence of venous thromboembolism during the months following the initial event. It was also well documented that heparin was most safely administered by continuous intravenous infusion and that adequate plasma concentrations in the first 48 hours were crucial in order to reduce the risk of later recurrences.